Pendampingan Peningkatan Keterampilan Pengadministrasian Arsip Digital dan Literasi Digital Pemuda Karang Taruna Pondok Sungai Abu: Pengabdian - Awal Khairi; Emelinda Emelinda; Eka Septiani; Mhd. Ikhsan; Efendi Efendi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Community service is helping to improve the skills of youth organizations in digital archive administration, ICT, and digital literacy. The methods used in implementing this program included direct mentoring, training, interactive discussions, and evaluation using post-tests and Focus Group Discussions (FGD). This training aimed to improve the skills and understanding of Karang Taruna youth regarding archive administration and the digital world. The results of the community service show that the youth successfully gained a deeper understanding of digital archive administration and improved their digital literacy skills. In addition, this program also created an atmosphere that supports the character development of the youth, provides practical experience, and prepares them to face the challenges of the working world.